A Statistical Analysis on Production of Chili and Its’ Prospect in Bangladesh - Hossen, Sayed Mohibul (Global Disclosure of Economics and Business, 2015)
Chili is one of the most significant marketable crops of Bangladesh. It is grown almost all over the country. There are more than 400 different varieties of Chili’s found all over the world. It is also called as hot pepper, sweet pepper, bell pepper, etc. Both chili and capsicum belong to same family as well as same genus that is Capsicum. C. frutescent is used for their small and very pungent fruits in hot sauces and as spices. It contains large amounts of vitamin C, small amounts of carotene (Provitamin A), vitamin B, vitamin B6, potassium, magnesium, and iron (USDA Nutrient Database). Bangladesh is one of the best producers, but there is no enough industry for preserving this fruit. So, all the production become indeed in consumption. The aim of the research is to know the cultural practices of chili in Bangladesh and how to make sweetened chili dishes that can play a vital role in our economy. This research considers the annual time series data for the period 2001-02 to 2010-11 and over seven divisions of Bangladesh. The data have been collected from various publications of BBS (Bangladesh Bureaus of Statistics) and BARC (Bangladesh Agriculture Research Council), the data of districts have been aggregated for seven divisions namely, Dhaka, Chittagong, Rajshahi, Khulna, Barisal, Sylhet, and Rangpur. Realizing the limitations of data availability, only nine variables are considered in the present research. Total production of Chili is taken as the dependent (endogenous) variable. The price of the Chili and seven divisions are considering as independent (exogenous) variables. The number of variables to be included in the model depends on the nature of the phenomenon under consideration and the purpose of the research.